Pemilu Kepala Daerah dalam Transisi Demokrasi - Zainal Arifin Hoesein (The Constitutional Court of the Republic of Indonesia, 2016)
The election of regional head has a strategic position to building democracy in transition. In order that the election of regional head can creating a dignified democracy, the implementation of its should be based on the principle of the general election i.e: independent, fair, equitable, rule of law; the orderly election, transparency, proportionality; professionalism, accountability, efficiency, and effectiveness.